2020
DOI: 10.1155/2020/6094126
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Adsorptive and Photodegradative Efficiencies of ZSM-11 Synthesized from Rice Husk Ash

Abstract: Rice husk was used to synthesize zeolite (ZSM-11). FTIR and X-ray diffraction methods were used to characterize the product. The synthesized zeolite was used to treat underground water from some communities in Cape Coast considering parameters such as total dissolved solids, total hardness, conductivity, nitrate, and phosphate. The percentage reduction in PO43− was 96.1% in Ebubonko and 92.5% in Apewosika. Similarly, the NO3− levels also decreased significantly in Kwaprow. The adsorption capability was also de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…With increased reactions time from 18 to 48 h, we observed that the intensity of the peak at 547 cm −1 was increased due to the percentage of aluminum insertion increases in the zeolite framework. 37 Hence, based on observed FT-IR and EDS results, it is concluded in this work that the synthesis of ZSM-11 zeolite type structure with MEL topology needs 3.17% of aluminum as well as 48 h for the completion of the reaction.…”
Section: Resultsmentioning
confidence: 66%
“…With increased reactions time from 18 to 48 h, we observed that the intensity of the peak at 547 cm −1 was increased due to the percentage of aluminum insertion increases in the zeolite framework. 37 Hence, based on observed FT-IR and EDS results, it is concluded in this work that the synthesis of ZSM-11 zeolite type structure with MEL topology needs 3.17% of aluminum as well as 48 h for the completion of the reaction.…”
Section: Resultsmentioning
confidence: 66%